Influence of ultrasound on the growth striations in GaₓIn₁₋ₓSb single crystals - Zolkina, L.V.; Kozhemyakin, G.N. (Functional Materials, 2005)
The results of investigation experiments of the growth striations in GaₓIn₁₋ₓSb single crystals with х=0.03 grown by Czochralski method with ultrasound field at a frequency of 1.44 MHz have been presented. It was noted that ultrasound eliminate the growth striations generated by the convection in the melt in the central part of the crystals and at the crystals periphery. The experimental results have been confirmed by the modeling experiments of the convection in the liquid phase in the conditions similar to growth conditions of Ga₀.₀₃ln₀.₉₇Sb single crystals.